The unbounded solution of a periodic mixed Sturm–Liouville problem in an infinite strip for the Laplacian - M.G. Elsheikh; V.N. Gavdzinski; T.G. Emam (Journal of the Egyptian Mathematical Society, 2013)
The unbounded solution, at the points where the boundary conditions change, for a mixed Sturm–Liouville problem of the Dirichlet–Neumann type can be obtained using the method of the integral equation formulation. Since this formulation is usually reduced to an infinite algebraic system in which the unknowns are the Fourier coefficients of the unknown unbounded entity, a study of ℓp-solutions imposes itself concerning the influence of the truncation on such systems. This study is achieved and the well-known theorem on the ℓ2-solutions of the infinite algebraic systems is generalized.